Peran Guru dalam Meningkatkan Minat Belajar Siswa di Kelas III SD Negeri 182/I Hutan Lindung Muara Bulian - Ahmad Sobari; Oktavioni Bastian; Listiana Listiana; Syahrial Syahrial; Silvina Noviyanti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The purpose of this study was to determine the teacher's role as a motivator in increasing the learning interest of third grade students at SD Negeri 182/I Hutan Lindung. This study uses a descriptive method with a qualitative approach. Data collection techniques carried out in this study were by means of observation, interviews and documentation. Based on the results of the study, there are ten ways that teachers do in carrying out their role as motivators. However, from the results of the research described above, there are only eight ways teachers can carry out their role as motivators. The eight ways are: using varied methods, creating competition, giving evaluations or tests, giving grades or numbers, notifying learning outcomes, giving prizes, giving praise, and giving punishment. Meanwhile, two ways that were not seen during the study were helping learning difficulties and forming good habits. Based on the results of the study, it can be concluded that the teacher's role as a motivator in increasing student interest in class III at SD Negeri 182/I Hutan Lindung, is 1) Using various methods, 2) Creating competition / competition, 3) Giving evaluation / test, 4 ) Giving grades or numbers, 5) Informing students' learning outcomes, 6) Giving gifts to students, 7) Giving praise, 8) Giving punishment if they don't do assignments.